How Useful Are Benefit Incidence Analyses of Public Education and Health Spending - Tiongson, Erwin (IMF Working Papers; Working Paper, 2003)
This paper provides a primer on benefit incidence analysis (BIA) for macroeconomists and a new data set on the benefit incidence of education and health spending covering 56 countries over 1960-2000, representing a significant improvement in quality and coverage over existing compilations. The paper demonstrates the usefulness of BIA in two dimensions. First, the paper finds, among other things, that overall education and health spending are poorly targeted; benefits from primary education and primary health care go disproportionately to the middle class, particularly in sub-Saharan Africa, HIPCs and transition economies; but targeting has improved in the 1990s. Second, simple measures of association show that countries with a more propoor incidence of education and health spending tend to have better education and health outcomes, good governance, high per capita income, and wider accessibility to information. The paper explores policy implications of these findings.